Executive social connections and gender pay gaps - Javakhadze, David; Shelton, Austin (Journal of Corporate Finance, 2022)
We examine whether managerial social capital, defined as aggregate benefits of social obligations and informal contacts accrued through social connections, influences gender pay gaps. Consistent with homophily, the tendency to bond and interact with others of similar type, we find a positive association between connections of male executives and compensation. However, these social ties do not enhance firm performance more than connections of female executives. We also demonstrate that connections reduce pay-for-performance sensitivity of male executives. Finally, we document a manifestation of homophily in other corporate decisions. Our findings are robust to model specifications and adjustments for potential endogeneity.